HEART BEAT SENSING SYSTEM FOR HEART ATTACK DETECTION - BADRUL HAIRI, NIZARUL HAZIM (2017)
This project will develop a heart rate sensing system for heart attack detection. It is aimed to help heart disease patients to detect a crucial situation when heart attack occurs and send alarm to an emergency contact so that a rapid follow up can be conducted during the heart attack. The final device of this project is expected to be able to monitor heart rate of patients, provide a warning signal to patients when the heart rate reaches a warning level and send an alarm to a registered number about the situation in a form of Short Message Service (SMS) or a call. This device also required to send the current location of the patient to the registered number. This project will use Arduino board as the microcontroller, a pulse sensor to measure the heart rate, a Global Service Mobile (GSM) module for sending SMS and call. This project also implements the Global Positioning System (GPS) module to provide the location.